2020
DOI: 10.1017/s1751731120001147
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot performance and rumen morphometrics of Nellore cattle adapted to high-concentrate diets over periods of 6, 9, 14 and 21 days

Abstract: The energy content of finishing diets offered to feedlot cattle may vary across countries. We assumed that the lower is the energy content of the finishing diet, the shorter can be the adaptation period to high-concentrate diets without negatively impacting rumen health while still improving feedlot performance. This study was designed to determine the effects of adaptation periods of 6, 9, 14 and 21 days on feedlot performance, feeding behaviour, blood gas profile, carcass characteristics and rumen morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
12
0
3
Order By: Relevance
“…During finishing, the cattle fed VM6 also had more meals per day and less DMI intake per meal in relation to the cattle fed VM14. Previous studies have reported that 6 days of adaptation resulted in no improvement in feedlot performance and negative effects on rumen epithelium development ( 1 , 4 ). As a result, despite the lack of VM effect on the HCW and ADG, the carcass fat deposition of the cattle fed VM6 was also negatively impacted by shortening the adaptation period.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…During finishing, the cattle fed VM6 also had more meals per day and less DMI intake per meal in relation to the cattle fed VM14. Previous studies have reported that 6 days of adaptation resulted in no improvement in feedlot performance and negative effects on rumen epithelium development ( 1 , 4 ). As a result, despite the lack of VM effect on the HCW and ADG, the carcass fat deposition of the cattle fed VM6 was also negatively impacted by shortening the adaptation period.…”
Section: Discussionmentioning
confidence: 97%
“…It is well-reported in the literature that the Nellore cattle fed MON can be safely adapted to high-concentrate diets for periods not shorter than 14 days (3)(4)(5). Therefore, this section aims to discuss the potential of adapting Nellore cattle to highconcentrate diets in 14 days using VM as the sole feed additive.…”
Section: Feed Additives Vs Adaptation For 14 Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…Estevam et al, (2020) evaluated increasing length of a step‐up protocol (6, 9, 14 and 21 days) utilizing cracked corn as the main energy source. It was reported that Nellore cattle adapted during 14 days presented greater final BW, average daily gain and hot carcass weight, as well as an improved gain:feed ratio compared to feedlot cattle adapted in the other lengths.…”
Section: Introductionmentioning
confidence: 99%
“…The time-lapse essential for the transition from high-forage to high-grain ration and vice-versa helps to establish a stable microbial community and results in significant metabolic changes in the rumen (Fernando et al 2010). This particular period adapts the animals in the form of structural changes in the rumen like ruminal papillae and functional changes in terms of the composition of ruminal microbiota (Estevam et al 2020). In the absence of a proper adaptation period, the animals may develop ruminal acidosis, ruminitis, and other health complications, which further hamper the animal production.…”
mentioning
confidence: 99%